THE EFFECT OF LEARNING INQUIRY TRAINING MODEL ON STUDENT LEARNING OUTCOMES ON MEASUREMENT MATERIALS - Felisa Irawani Hutabarat; Rita Juliani (Universitas Negeri Medan, 2017)
This research aims to know the effect of learning model of inquiry learning results students training material measurement. This type of research is quasi experiment. Sampling done by cluster random sampling by taking 2 classes from grade 9 i.e. class X SCIENCE experiments as a class-B that add up to 35 people and class X SCIENCE-C as control classes that add up to 35 people. The instruments used to find out the results of student learning is the learning outcomes tests have been validated in multiple choice form numbered 15 reserved and activity sheets students. The results of the value obtained 37.71 pretes and postest 70.11. The t-test analysis retrieved thitung greater than ttabel so that it can be concluded no difference due to the influence of the learning model of inquiry learning results students training material measurement.